TRANSCENDING THE WESTERN PARADIGMS: RECLAIMING THE INDIAN TEXTS THROUGH ‘COSMOCAL PREADING’ - Anshuman, Praveen Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The body of the Indian Classical Literature, embodying cultural, spiritual, and philosophical deliberation, remains an emblem of the subcontinent’s intellectually charged tradition. Therefore, the approach to read and interpret all such texts has often been spoiled by the modern approaches and pedagogical distortions, obscuring the true essence lying within. This paper seeks to understand the multifarious richness of Indian Classical Literature, examining the pedagogical pitfalls and proposing alternative approaches—such as encapsulated in ‘Cosmocal Preading’ (Cosmic + Local and Pre + Reading)—to genuinely engage with such texts. By critiquing the paradigms set by the Eurocentrism that define modernity and emphasize the epistemological framework rooted in Indian esoteric literature, this research paper aims to establish a more holistic, multidimensional understanding of the Indian classics. Furthermore, the paper discusses how terms like Dharma, Karma, Moksha and rebirth, crucial to texts like the Mahābhārata and others, must be comprehended within their own cultural and philosophical contexts rather than through reductive or misaligned or rather say distorted frameworks. This paper thus advocates for the re-education of both readers and scholars on how to approach classical texts in a way that honours their intended depth and universality.